(untitled) (Research, Society and Development, 2021)
Most traditional methods are only used to remove free oil from wastewater, and they are not efficient for separating oil-water emulsions. The adsorption separation process can be widely applied for the treatment of emulsions, mainly due to the cost and benefit of the process and the wide variety of materials that can be used as adsorbents, for example activated carbon, clays, zeolites, etc. Among the various types of porous materials called "Metal Organic Frameworks" (MOFs) are the zeolitic imidazolate (ZIFs) structures. The zeolitic structure of the ZIFs allows to exhibit high surface areas and thus to be promising adsorbents. To evaluate the adsorption capacity of ZIF-8 in the removal of emulsified oil, ZIF-8 was synthesized using Zn metal and as organic binder 2-methylimidazole (Hmim), dissolved in methanol at room temperature. ZIF-8 was characterized by X-ray diffraction (XRD) technique to determine the crystalline structure. To evaluate the capacity of the emulsified oil, a pH-influence test and chemical kinetics were determined. The best pH of the emulsion for removal was pH 6. The chemical kinetics performed at pH 6 presented the best fit with the pseudo-second model with correlation coefficient 0.93. According to the kinetic data, a removal percentage of 92.43% was found with only 30 min of removal.